Consumer preference of food pairing tea: Sensory approach - Dase Hunaefi; Inas Zahidah; Zulfa Nur Hanifa; Philipp Fuhrmann; Iryna Smetanska (jurnal1, 2022)
Food pairing is a method for identifying the suitability of certain foods and drinks with each other. The current study aimed to investigate how many different food items can be combined with tea as well as the characteristics of these food items. The research was conducted by stages, including an online survey of the most popular tea companion food products, a focus group discussion, and sensory tests using the Check-All-That-Apply (CATA) method. The survey respondents liked the combination of sweet tea and biscuits. Approximately 30 consumer panelists tasted sweet tea and three kinds of coconut biscuit together and then determined the preferred attributes of the combination. CATA results showed that the preferred attributes of consumers in the ideal combination are buttery, creamy, coconut savory, sandy, and sweet. The product pair closest to the ideal is tea with “Biscuit B” (T-B), the combination of which can increase sweetness, raise buttery and creamy mouthfeel, and decrease sandy texture.